1990
DOI: 10.1093/jn/120.7.668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propionate on Lipid Biosynthesis in Isolated Rat Hepatocytes

Abstract: The effects of propionate, a product of intestinal fiber fermentation, on fatty acid and sterol synthesis were studied in isolated rat hepatocytes. Fatty acid synthesis, as measured by tritium incorporation from 3H2O, was inhibited in the presence of 1 mmol/L propionate with no substrate additions or additions of acetate, butyrate, lactate or oleate. Incorporation of [1-14C]acetate into fatty acids was also inhibited in the presence of propionate. Although propionate markedly depressed [1-14C]acetate incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
101
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(109 citation statements)
references
References 24 publications
7
101
1
Order By: Relevance
“…Another recent study suggested a role for differences in intestinal methane production in altered glycemic control in diabetic subjects [34], further supporting our finding of altered glucose levels in methane-producing individuals, and methane producers have also been shown to have higher fasting serum cholesterol concentrations when compared to age-, sex-, and BMI-matched non-methane producers. The alteration between systemic availability of acetate and propionate produced during carbohydrate fermentation by methanogenic archaea has been suggested to influence doi: 10.7243/2053-3640-2-2 the blood lipid levels [35][36][37]. Using an animal model and ex vivo studies, our group has also shown that methane may also directly affect intestinal transit and gut neuromuscular function [38], findings which have since been confirmed by an independent group [39].…”
Section: Discussionmentioning
confidence: 60%
“…Another recent study suggested a role for differences in intestinal methane production in altered glycemic control in diabetic subjects [34], further supporting our finding of altered glucose levels in methane-producing individuals, and methane producers have also been shown to have higher fasting serum cholesterol concentrations when compared to age-, sex-, and BMI-matched non-methane producers. The alteration between systemic availability of acetate and propionate produced during carbohydrate fermentation by methanogenic archaea has been suggested to influence doi: 10.7243/2053-3640-2-2 the blood lipid levels [35][36][37]. Using an animal model and ex vivo studies, our group has also shown that methane may also directly affect intestinal transit and gut neuromuscular function [38], findings which have since been confirmed by an independent group [39].…”
Section: Discussionmentioning
confidence: 60%
“…It has also been suggested that hypocholesterolemic effect of dietary fi bres might also be mediated by the short chain fatty acids from fi bre fermentation. Propionate is reported to inhibit fatty acid metabolism, which plays a key role in the synthesis of cholesterol (Nishina and Freeland 1990, Wright et al 1990, Demignè et al 1995.…”
Section: Dietary Fi Bre and Health Benefi Tsmentioning
confidence: 99%
“…Our results showed that propionate prevented cellular TG accumulation in YAMC cells through the induction of PPARa expression. Evidence has been accumulating that propionate has fatty acid-lowering effects through the inhibition of fatty acid production in the liver (24). Additionally, the decreases in fatty acid levels by propionate probably derive from the inhibition of lipolysis and the induction of adipogenesis in adipose tissue (25).…”
Section: Discussionmentioning
confidence: 99%